Peran Rencana Makanan Visual dalam Meningkatkan Pengetahuan tentang Perencanaan Menu, Perilaku Pembelian Makanan, dan Mengurangi Pemborosan Makanan di Rumah Tangga di Kota Bogor - Elysia Rafa Azzahrah; Prita Dhyani Swamilaksita (PT.Mantaya Idea Batara, 2026)
Background: Household food waste presents a significant barrier to sustainable food security, with notable environmental, economic, and nutritional implications. This study evaluated the effectiveness of visual meal-planning education in enhancing knowledge of menu planning, influencing food purchasing behavior, and reducing household food waste in Tanah Sareal District, Bogor City. Methods: A pre-experimental, one-group pretest–posttest design was employed with 50 housewives responsible for household food management, selected through total sampling. The intervention included an initial educational session and refresher sessions every four weeks over a 12-week period, utilizing visual meal-planning materials. Data collection involved structured questionnaires to assess knowledge and behavior, as well as direct measurement of food waste using a weighing method over eight consecutive days. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. Results: Findings indicated a significant increase in knowledge scores at the third evaluation (p = 0.001), reflecting improved understanding of menu planning and food purchasing. While planning and purchasing behaviors improved, the changes were not statistically significant. However, householdfood waste decreased significantly by 41 g/capita/day (60%) following the intervention (p = 0.000). Conclusion: In summary, visual meal-planning education effectively enhances knowledge and substantially reduces household food waste, although its influence on behavior change is limited.